Patient predictors of response to cognitive behaviour therapy and schema therapy for depression. (September 2018) - Carter, Janet D; McIntosh, Virginia VW; Jordan, Jennifer; Porter, Richard J; Douglas, Katie; Frampton, Christopher M; Joyce, Peter R
Objective: Few studies have examined differential predictors of response to psychotherapy for depression. Greater understanding about the factors associated with therapeutic response may better enable therapists to optimise response by targeting therapy for the individual. The aim of the current exploratory study was to examine patient characteristics associated with response to cognitive behaviour therapy and schema therapy for depression. Methods: Participants were 100 outpatients in a clinical trial randomised to either cognitive behaviour therapy or schema therapy. Potential predictors of response examined included demographic, clinical, functioning, cognitive, personality and neuropsychological variables. Results: Individuals with chronic depression and increased levels of pre-treatment negative automatic thoughts had a poorer response to both cognitive behaviour therapy and schema therapy. A treatment type interaction was found for verbal learning and memory. Lower levels of verbal learning and memory impairment markedly impacted on response to schema therapy. This was not the case for cognitive behaviour therapy, which was more impacted if verbal learning and memory was in the moderate range. Conclusion: Study findings are consistent with the Capitalisation Model suggesting that therapy that focuses on the person's strengths is more likely to contribute to a better outcome. Limitations were that participants were outpatients in a randomised controlled trial and may not be representative of other depressed samples. Examination of a variety of potential predictors was exploratory and requires replication.